2017
DOI: 10.1002/star.201600344
|View full text |Cite
|
Sign up to set email alerts
|

Rheology, thermal properties, and microstructure of heat-induced gel of whey protein-acetylated potato starch

Abstract: The objective of the present work was to investigate the effects of acetylated potato starch (APS) on the rheological and thermal properties and the microstructure of a heat‐induced gel of whey protein isolate (WPI) using small‐amplitude oscillatory rheometry, differential scanning calorimetry (DSC), dynamic light scattering (DLS), and scanning electron microscopy (SEM). The rheological results indicated that the elastic (G′) and viscous modulus (G″) of the WPI–APS systems increased as the concentrations of AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 47 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…DSC heating curves for acetylated potato starch-whey protein blended systems have shown two obvious peaks, reported to represent acetylated potato starch gelatinization (about 61 °C) and whey protein denaturation (about 73 °C) (Ren et al, 2017). However, single endothermic peaks for other starch-protein blends have also been reported in other studies (Lu et al, 2016;Yang et al, 2019).…”
Section: Thermal Propertiesmentioning
confidence: 79%
See 1 more Smart Citation
“…DSC heating curves for acetylated potato starch-whey protein blended systems have shown two obvious peaks, reported to represent acetylated potato starch gelatinization (about 61 °C) and whey protein denaturation (about 73 °C) (Ren et al, 2017). However, single endothermic peaks for other starch-protein blends have also been reported in other studies (Lu et al, 2016;Yang et al, 2019).…”
Section: Thermal Propertiesmentioning
confidence: 79%
“…Furthermore, various studies have shown that proteins alone or combined with polysaccharides (e.g. inulin, native starch, or acetylated starch) can produce gel matrices with different microstructures, thereby improving their water-retention, rheological, and texture properties (Nieto-Nieto et al, 2015;Ren, Dong, Yu, Hou, & Cui, 2017;Ren & Wang, 2019;Yu, Ren, Zhao, Cui, & Liu, 2020).…”
Section: Proteinmentioning
confidence: 99%
“…The EPS‐YW11/WP at different ratios exhibited three‐dimensional network structure at 25 °C, which became more branched and porous at higher temperatures (60, 90 °C), and with more proportion of the EPS in the complexes. However, the local reaction was lagging behind, resulting in uneven distribution of the microstructure of the polymer complexes (Ren & Dong, 2017). WP could expose amino groups after denaturation at 90 °C, and it was more conducive to the carbonyl ammonia reaction, thus forming more uniform porous structure (Ren & Wang, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The rheology of whey protein isolate and casein micelles (MC) mixtures upon heating has been evaluated, indicating that WPI binds to MC and strengthens the junctions of the MC network [176]. Likewise, different mixtures, including starch, rice, or other polysaccharides, or other proteins combined with WPI are currently being studied, aiming to improve the structural and functional properties (e.g., strength, viscosity) of protein solutions [176,182].…”
Section: Whey Proteins: Research Insights and Trendsmentioning
confidence: 99%
“…Characterization of WP gelation profiles has been recently studied; however, the main challenge remains in the production of effective WP microgel systems to overcome brittleness and susceptibility to syneresis [183]. Research is focusing on the ability of WP to form hydrogels that entail specific structural and sensory characteristics for targeted food products like yoghurt, ice cream, bakery products, desserts, and meat products [182]. Understanding the interactions of whey with other biopolymers is crucial in the sense of novel functional food properties.…”
Section: Whey Proteins: Research Insights and Trendsmentioning
confidence: 99%